2021
DOI: 10.1007/s11666-021-01185-z
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Wear of Conventional and Suspension Sprayed Nanocomposite WC-Co Coatings: An Invited Review

Abstract: The global thermal spray coatings market was valued at USD 10.1 billion in 2019 and is expected to grow at a compound annual growth rate of 3.9% from 2020 to 2027. Carbide coatings form an essential segment of this market and provide cost-effective and environmental friendly tribological solutions for applications in aerospace, industrial gas turbine, automotive, printing, oil and gas, steel, and pulp and paper industries. Almost 23% of the world’s total energy consumption originates from tribological contacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 149 publications
0
29
0
Order By: Relevance
“…Figure 2 shows some of the coating particle temperatures and velocity ranges achievable by thermal spray processes. [11] The particle velocity which can be achieved during the thermal spray process (Figure 2) ranges from %20 to %1050 m s À1 , which influences the mechanical, thermal, and EM properties due to the extent of the 1) designed phase transformation, for example, ratio of amorphous-tocrystalline phase for hydroxyapatite (Ca 5 (PO 4 ) 3 (OH)) coatings for biomedical applications [12,13] and controlled degree of eta phase (i.e., carbon-deficient form of WC that results in a harder or brittle cemented carbide) formation for sliding wear applications of WC-Co coatings, [9] etc., and 2) control of porosity during deposition. [14] Complex feedstock materials such as BaCoTiFe 10 O 9 , SrFe 12 O 9 , and hydroxyapatite [12,15,16] can be thermally sprayed using the correct powder chemistry, coating process, and coating process parameters.…”
Section: Thermal Spray Coatings As a Manufacturing Route For Em Mater...mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 shows some of the coating particle temperatures and velocity ranges achievable by thermal spray processes. [11] The particle velocity which can be achieved during the thermal spray process (Figure 2) ranges from %20 to %1050 m s À1 , which influences the mechanical, thermal, and EM properties due to the extent of the 1) designed phase transformation, for example, ratio of amorphous-tocrystalline phase for hydroxyapatite (Ca 5 (PO 4 ) 3 (OH)) coatings for biomedical applications [12,13] and controlled degree of eta phase (i.e., carbon-deficient form of WC that results in a harder or brittle cemented carbide) formation for sliding wear applications of WC-Co coatings, [9] etc., and 2) control of porosity during deposition. [14] Complex feedstock materials such as BaCoTiFe 10 O 9 , SrFe 12 O 9 , and hydroxyapatite [12,15,16] can be thermally sprayed using the correct powder chemistry, coating process, and coating process parameters.…”
Section: Thermal Spray Coatings As a Manufacturing Route For Em Mater...mentioning
confidence: 99%
“…[166] While there are numerous examples where material has been doped with REEs using techniques other than thermal spray to improve EM wave propagation characteristics, such as chemical coprecipitation [167] or hydrothermal synthesis, [156] it is also possible that doping certain REEs during thermally sprayed coatings could also help improve the EM propagation wave characteristics of materials. In an example, Bartuli, Cipri and Valente (2008) [70] used a range of complex ceramic-based composite coatings, which included lanthanum/La REE (e.g., Cr 2 O 3 þ La 0.5 Sr 0.5 MnO 3 40wt%, Cr 2 O 3 þ Al 20 wt% þ La 0.5 Sr 0.5 MnO 3 20wt%) fabricated by air plasma spraying to evaluate their tailored EM properties (essentially as absorbers in the microwave range (8)(9)(10)(11)(12)). However, thermal spraying can make REEs prone to oxidation during processing and operation, and oxidation can lead to brittle coatings and deterioration of magnetic properties.…”
Section: Materials Doped With Rare Earth Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the apparent dense microstructure of HVOF coatings, the electrochemical tests generally reveal that the as-sprayed metal coatings could not provide the substrate with effective and reliable protection from corrosion due to the existence of unbonded lamellar interfaces (Ref 25 , 26 ). Moreover, limited bonding also degrades the wear performance of hard alloy coatings since lamella spalling occurs easily through the propagation of sub-surface cracks along the lamellar interface at high stress conditions (Ref 24 , 27 ), especially as the coatings are subjected to dynamic loading (such as cavitation erosion) (Ref 28 ). Hiraga et al reported that compared with vacuum plasma-sprayed NiTi coating the laser remelting treatment leading to the formation of bulk-like NiTi presented the enhanced cavitation erosion resistance by a factor of magnitude from one order to over two orders (Ref 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%